Comparing multistate expected damages, option price and cumulative prospect measures for valuing flood protection. Issue 5 (28th May 2013) - Farrow, Scott; Scott, Michael
Key Points: The key choice is between non‐expected and expected utility measures. Continuous event modeling is useful The basic non‐expected utility value is less than the expected utility value Abstract : [1] Floods are risky events ranging from small to catastrophic. Although expected flood damages are frequently used for economic policy analysis, alternative measures such as option price (OP) and cumulative prospect value exist. The empirical magnitude of these measures whose theoretical preference is ambiguous is investigated using case study data from Baltimore City. The outcome for the base case OP measure increases mean willingness to pay over the expected damage value by about 3%, a value which is increased with greater risk aversion, reduced by increased wealth, and only slightly altered by higher limits of integration. The base measure based on cumulative prospect theory is about 46% less than expected damages with estimates declining when alternative parameters are used. The method of aggregation is shown to be important in the cumulative prospect case which can lead to an estimate up to 41% larger than expected damages. Expected damages remain a plausible and the most easily computed measure for analysts.